The Effect of Circuit Training on Improving the Shooting Ability of BMJN SSB Players - Ulya, Azzikri; Fitrah, Akrimatul Aulya; Prawibowo, Muhammad; agim huda kusuma; ruzie gustamen randa (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2025)
This study aims to determine the effect of circuit training on improving the shooting ability of SSB BMJN players. Shooting is a fundamental technique that significantly determines goal-scoring success, so effective training methods are needed to improve kicking power, accuracy, and speed. Circuit training was chosen because of its characteristic of combining several forms of physical exercise in sequence, so that it can train various fitness components at once, such as muscle strength, endurance, coordination, and power, which have a direct contribution to shooting performance. This study used an experimental method with a one-group pretest-posttest design. The subjects were SSB BMJN youth players selected based on age uniformity, playing experience, and relatively similar physical condition. A circuit training program was implemented over several weeks with structured intensity and progression. Shooting ability measurements included shot accuracy, ball speed, and shot consistency on specific targets. The results of this study showed a significant improvement in shooting ability after implementing circuit training, both in terms of accuracy and kick power. This improvement was supported by physical adaptations resulting from the repetitive and planned training load. Therefore, it can be concluded that circuit training is an effective method for improving the shooting ability of soccer players, particularly those at SSB BMJN. This method is recommended in routine training programs to optimize the performance of players' basic techniques.